Utilização de silício, óleos essenciais e extratos como alternativas no manejo integrado de Gonipterus platensis (Coleoptera: Curculionidae) em Eucalyptus spp. - Galvan, Camila Fonseca (2024)
Worldwide, the eucalyptus weevil, Gonipterus platensis, native to Australia, is an invasive insect pest, causing defoliation and significant damage to the Eucalyptus genus. Control of this pest is carried out mainly with the egg parasitoid Anaphes nitens, however in some countries the efficiency rate is reduced, while chemical products are not registered for this pest in Brazil. Therefore, the general objective of the work was to identify alternatives for controlling G. platensis, generating two specific objectives corresponding to each study, which consisted of: a) evaluating the effect of silicate foliar fertilization on the physiological condition of the hybrid Eucalyptus urophylla x E. globulus the control of G. platensis; and b) investigate the effects of essential oils and extracts in controlling this insect pest. The specimens used were collected in São Francisco de Assis in southern Brazil (29º34'20”S, 55º15'36”W) and kept in cages with eucalyptus branches for laboratory feeding. For the experiments with silicate foliar fertilization, three concentrations were used and the control, in which the hybrid plants were sprayed until the leaves were completely moist. At 7, 14 and 21 days after application (a.d.), evaluations were carried out to determine the response time of silicate fertilizer in reducing herbivory by G. platensis. The application of 20 mL L-1 and 30 mL L-1, 21 d.a.a provided less loss of leaf area, bing suitable for preventive use. For the second study, the following were used: a) essential oil (EO) from Eucalyptus benthamii b) EO from Eugenia uniflora; c) crude extract (EB) of Eucalyptus benthamii and pyroligneous extract, the first two at concentrations of 0.5, 1, 2, 4 and 6% and the last two at concentrations of 5, 10, 15, and 20%. The EOs of Eugenia uniflora and Eucalyptus benthamii were efficient in reducing the herbivory of G. platensis, while the crude extract of Eucalyptus benthami has insecticidal potential on G. platensis adults under laboratory conditions.